The No2 Gas Welding Exposure with Saturation Oxygen Levels in Commerce - Dewi Anggun Nofrianti (JURNAL KESEHATAN LINGKUNGAN, 2017)
Welding is one of the basic process in the manufacture of an item with metal material. This process have a risk that can be dangerous. One of the risk is the gas poisoning. NO2 gas can decrease the oxygen level in the body. This is because NO2 gas have corrosive characteristic for body and can causes infection in respiratory tract. The purpose of this study is to describe the levels of NO2 exposure on welding process with oxygen saturation levels in employees in the commerce division welding at PT PAL Indonesia (Persero). The design of this research is a cross sectional study. The sample in this study was 9 welding employees, whereas the control variables in this study is 9 respondents that were not exposed from NO2 gas. Sample was taken with purposive sampling method that restricted with criteria that have been set. The independent variable was NO2 level, while the dependent variable was oxygen saturation level in the blood. This research was descriptive research. The results of this research showed the oxygen saturation levels at commerce division employees of PT PAL Indonesia (Persero) in normal value that is between 95-100% and the rate of NO2 gas in the commerce division area of PT. PAL Indonesia (Persero) is under the threshold value that has been set. Conclusions in this study was gas exposure not exceeded the threshold value and the employees had normal of oxygen saturation levels. So it is needed to do routine monitoring about the levels of NO2 gas to reduce the risk of exposure. as well as make more green space in the welding area.